A Method of Reducing Salt Content in Fermented Soy Sauce Improves Its Flavor and Quality - Shuang Zheng; Zhenbin Zhang; Xiuli Zhao; Wanning Li; Lihua Hou (Foods, 2024)
Most commercially available soy sauce is fermented by high-salt liquid-state (HS) fermentation, which has an excessive salt content and a long fermentation period. In this study, a new salt-reduced fermentation (SR) soy sauce technology involving multiple strains of bacteria was developed to reduce consumers’ salt intake. The SR soy sauce was found to have an amino acid nitrogen content of 8.40 g/L and over 80 kinds of flavor substances, which were significantly higher than those of low-salt solid-state fermented soy sauce and approximately equal to HS soy sauce. Compared with HS soy sauce, the salt content of the SR soy sauce was reduced by 59.2%, achieving the salt reduction goal. The proportion of umami amino acids in SR soy sauce reached 32.0% of the total level, enhancing SR soy sauce’s quality. Hence, the new fermentation process can decrease salt content and shorten fermentation time.